2015
DOI: 10.1097/qad.0000000000000797
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antidepressant treatment on HIV and depression outcomes

Abstract: Background Depression is a major barrier to HIV treatment outcomes. Objective Test whether antidepressant management decision support integrated into HIV care improves antiretroviral adherence and depression morbidity. Design Pseudo-cluster randomized trial. Setting Four US infectious diseases clinics. Participants HIV-infected adults with major depressive disorder. Intervention Measurement-Based Care: depression care managers used systematic metrics to give HIV primary-care clinicians standardized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 54 publications
2
49
0
1
Order By: Relevance
“…56 Future research may consider the feasibility of incorporating an internalized stigma reduction component into an existing and efficacious behavioral intervention for depression and adherence, 57 or in combination with a medical intervention for depression, which have achieved clinically significant improvements in symptoms of depression but have had limited effects on ART adherence. 58 …”
Section: Discussionmentioning
confidence: 99%
“…56 Future research may consider the feasibility of incorporating an internalized stigma reduction component into an existing and efficacious behavioral intervention for depression and adherence, 57 or in combination with a medical intervention for depression, which have achieved clinically significant improvements in symptoms of depression but have had limited effects on ART adherence. 58 …”
Section: Discussionmentioning
confidence: 99%
“…110,134 Depression treatment improved ART adherence 150 and HIV outcomes 151 ; however, 3 US-based randomized clinical trials of antidepressant treatment showed no effect on ART adherence. 152154 More intensive behavioral interventions integrating depression and adherence counseling showed improvement in both outcomes. 155157 …”
Section: Engagement In Care and Art Adherencementioning
confidence: 98%
“…PLWH experience a high symptom burden that can be hard to manage, but can be improved with engagement in healthy self-management behaviors such as exercise (Barroso & Voss, 2013; Pence et al, 2015; Watkins & Treisman, 2015). In addition to improving health, developing interventions that help PLWH engage in regular, moderate-to-vigorous exercise and eating a healthy, balanced diet, are likely to have a significant effect on symptom burden.…”
Section: Discussionmentioning
confidence: 99%